Early Life Bereavement and Schizophrenia: A Nationwide Cohort Study in Denmark and Sweden. Issue 3 (January 2016) - Liang, Hong; Olsen, Jørn; Yuan, Wei; Cnattingus, Sven; Vestergaard, Mogens; Obel, Carsten; Gissler, Mika; Li, Jiong
Abstract : Abstract: We aimed to examine whether early life bereavement, as indicator of severe stress, was associated with an increased risk of schizophrenia later in life. Based on population registers, we established a cohort of all children born in Denmark (N = 1 686 416) and Sweden (N = 2 563 659) from 1973 to 1997. Children were categorized as exposed if they lost a first-degree relative during the first 18 years of life. Outcome is the first diagnosis of schizophrenia as either inpatient or outpatient. Log-linear Poisson regression models were used to estimate incidence rate ratios (IRRs). A total of 188, 850 children (4.6%) experienced death of a first-degree relative from birth to 18 years of age. Compared with unexposed children, those exposed had overall a 39% higher risk of schizophrenia (= 1.39, 95% CI [confidence interval]: 1.32–1.47). The IRR was particularly high if the family member committed suicide (aIRR = 2.11, 95% CI: 1.90–2.34) or died due to an injury or accident (aIRR = 1.44, 95% CI: 1.27–1.63). The IRR of schizophrenia decreased with increasing child's age at bereavement ( P  < 0.0001). Children who experienced >1 death during the first 18 years of life (aIRR = 1.79, 95% CI: 1.46–2.19) had a higher risk than those with a single death (aIRR = 1.37, 95% CI: 1.30–1.45). The study suggested that exposure to death of a first-degree relative before 18 years was associated with an increased risk of schizophrenia in later life. The complex mechanisms behind these associations remain to be elucidated. Abstract : Supplemental Digital Content is available in the text